Crypts in Asymmetric Fission in Endoscopic Biopsies from German Patients With Inflammatory Bowel Disease - Rubio, Carlos A.; Lang-Schwarz, Corinna; Vieth, Michael (Anticancer Research, 2021)
Background/Aim: We previously found in Swedish patients with inflammatory bowel disease (IBD), crypts in symmetric fission (CSF) and in asymmetric fission (CAF). This study aimed to examine CSF and CAF in a cohort of German patients with IBD. Patients and Methods: H&E-sections from 106 IBD-patients [59 ulcerative colitis (UC) and 47 Crohn colitis (CCs)] were analysed. Results: A total of 588 crypts in fission (CF) were found; 342 (58.2%) in UC and 246 (41.8%) in CCs. Out of the 505 CAFs found, 304 (60.2%) were recorded in UC, and 201(39.8%) in CCs (p=0.15272). Conclusion: Despite that German and Swedish populations reside in disparate geographical regions with different ecological milieus, the proportions of CAF and CSF were similar, thereby suggesting that CAF and CSF develop in IBD independently of the local environmental conditions in the two regions.
CRIS-Team WoS Importer:2021-12-03